(untitled) (One Health & Risk Management, 2023)
Traumatic injuries and violence pose a staggering burden to human health and well-being throughout the world. Injuries are a leading cause of death for all age groups but disproportionately affect the young. These deaths, caused by injuries such as road traffic crashes, drowning or falls, and violence including homicide and self-directed violence, end lives early and traumatize families and communities. Compared to injury deaths, non-fatal injuries are far more common and can cause disability, lead to high medical expenditures, and psychological trauma. Injuries are inequitably distributed within and across countries. Globally, injury death rates are highest in Low and LowMiddle income countries. And, within any specific country, injury incidence is higher in low-resource communities and for under-served populations. There are many causes of this inequity, including dangerous environments, low health literacy, and lack of access to trauma care. Perhaps one of the most compelling reasons to prioritize research on traumatic injuries and violence is that injuries are preventable. Preventing injuries reduces medical expenditures, improves work readiness, and decreases the number of people living with or caring for people with physical, psychological, or cognitive disabilities caused by trauma, to name just a few prevention impacts. There are many strategies to prevent injuries. Environmental modification strategies range from how we design roadways and vehicles to how we build urban environments to reduce crime. Many of these environmental approaches have other benefits, such as reducing transportation time or increasing community cohesion. Policy strategies can help prevent injuries, such as policies that require workplaces to use safe equipment or can help reduce their burden, such as policies that help cover medical costs of those with injury-related disabilities. Behavioral strategies can reduce injuries throughout the lifespan, starting with programs for parents that reduce child abuse and maltreatment through fall prevention programs for the elderly. All of these approaches work together to create a strong safety culture, and research that advances the evidence base for injury prevention is a critical component of safety culture. This special issue highlights strong emerging research in injury and violence and will accelerate progress in saving lives being lost from trauma. Although knowledge about the burden of injuries and violence, their causal mechanisms, and evidence-based prevention approaches is growing, the field of injury and violence prevention has not received the level of research investment equal to the burden on society. This issue will advance our knowledge about the prevalence of different types of injuries and violence and will identify important components for future prevention efforts. To conduct this research, research teams have invested in improving data quality, applying new methodologic approaches, and have built new research collaborations. This work is possible because of a partnership called iCREATE: Increasing Capacity for Injury Research in Eastern Europe. This partnership between leading research universities in Armenia, Georgia, Moldova, Romania, and the US and funded by the National Institutes of Health-Fogarty Center in the US, has had a substantial impact in a building research capacity, establishing curriculum, training students, and promoting a safety culture, and it has helped collaborative research teams work together to reduce the high burden of injuries and violence.